COMPARISON OF THE PARASITE COMMUNITIES OF NOTOTHENIA ROSSII RICHARDSON, 1844 (PISCES: NOTOTHENIIDAE) AMONG THREE ANTARCTIC LOCALITIES - Larenas-Órdenes, Catalina (2022)
This study describes the parasite communities of the fish Notothenia rossii Richardson, 1844 at two Antarctic localities, the Northern Peninsula Antarctic Area (NPA), and Greenwich Island (IGR). In addition, data from Muñoz and Rebolledo (2018) collected from a third locality, King George Island (IRJ). Abundance and species richness of parasite infra-communities, and parasite composition were compared between these three localities. Total length of hosts was included in the analyses. Nineteen parasite species were found in N. rossii at NPA and IGR. Most of the species had already been recorded in IRJ. The acanthocephalans Metacanthocephalus johnstoni Zdzitowiecki, 1983 and Aspersentis megarhynchus (von Linstow, 1892), and the digeneans of Macvicaria spp. were the most prevalent and dominant species at different localities, IRJ, NPA and IGR, respectively. Infra-community parasite abundance was significantly different between IRJ and NPA, while parasite richness was similar among the three localities. The total length of N. rossii from IRJ was significantly higher than the other two localities. Parasite abundance and species richness were significantly correlated with the fish total length, except the parasite richness at NPA. The Jaccard similarity index between pairs of localities was between 65% and 76%. However, the great abundance differences among parasitespecies resulted in fish having different proportions in parasite composition between IRJ and IGR. This finding was not due to differences in host total length, but indicates that biotic and abiotic conditions are disparate, and therefore, ecosystem dynamics differ between those localities.